Analisis Kelayakan Biaya dan Manfaat Investasi Teknologi Informasi Digital Advertising pada Google Merchandise Store - Raka Rachmanda Putra; Andi Reza Perdanakusuma; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Google Merchandise Store is a business unit owned by Google in form of e-commerce that sells merchandise made by Google like clothing, bag, stationary, and others. As a business process support, Google Merchandise Store did an investment in digital marketing. Google Merchandise store spend some of money in form of investment to digital advertising service provider called Google Ads to get visitors, reach, or conversion from paid search and or display ad networks. Researchers use web traffic report from Google Analytics to analyze its investment feasibility using Alinean ROI Dashboard concept. Alinean ROI Dashboard combine tangible and intangible benefits with risk factor and calculate them using metrics such as ROI, NPV, Payback Period, and other to represent investment feasibility. Based on the analysis result, investment that is conducted by Google Merchandise Store has Risk Adjusted ROI at 110,57%. But after using periodical report that represented as linear diagram, researcher found there is a degradation trend at 19,5% each period so that company should consider investment influencing factors if they decide to continue its investment in digital advertising.